An Analysis On 7th Grade Students’ Reading Comprehension Through Skimming- Scanning Techniques - Dewi, Kadek Ayu Astari (English Education Department STKIP Agama Hindu Singaraja, 2022)
This research was purposed to describe students’ reading comprehension through skimming-scanning technique at SMPN 6 Singaraja and to describe supporting and limiting factors in implementing skimming and scanning for the 7th grade students’ reading comprehension in SMPN 6 Singaraja. Descriptive qualitative research is the method employed in this investigation. Teachers and students were the focus subject of this investigation. The result showed that the supporting factor in implementing skimming and scanning for the students’ reading comprehension in 7th grade SMPN 6 Singaraja is the technique is easy to use for certain text. The limiting factor in implementing skimming and scanning for the students’ reading comprehension in 7th grade SMPN 6 Singaraja is the students’ limited vocabulary which mean needs vocabulary enrichment. Then, the 7th grade students’ reading compprehension through skimming-scanning technique implemented in reading in SMPN 6 Singaraja are categorized as good with mean score 75.5.